Effect of online tDCS to left somatomotor cortex on neuropsychiatric symptoms among older adults at risk for dementia. (February 2023) - Turnbull, Adam; Anthony, Mia; Tadin, Duje; Porsteinsson, Anton P.; Heffner, Kathi; Lin, Feng V.
Abstract: Background: Neuropsychiatric symptoms (NPS) in mild cognitive impairment (MCI) cause distress to patients and caregivers, and accelerate progression to dementia. Transcranial direct current stimulation (tDCS) is a promising non-invasive treatment for NPS. Objective/hypothesis: This pilot study assessed behavioral and neural effects of a 4-week anodal tDCS intervention targeting left sensorimotor cortex (LSMC: left precentral/postcentral gyri) during visual attention (compared to online sham tDCS), in 40 older adults (24 females, mean age = 71) with MCI. Methods: A phase 0 double-blinded randomized control trial was conducted. NPS (patient-reported mood symptoms plus a caregiver-reported questionnaire) and fMRI were measured at baseline and immediately post-intervention. Results: Generalized Estimating Equations found no significant group by time interactions for either NPS measure. However, there was evidence of decreased patient-reported NPS (Wald's χ 2 = 3.80, p = .051), decreased LSMC activation during visual attention (Wald's χ 2 = 2.93, p = .087), and increased LSMC-amygdala resting-state functional connectivity (rsFC; Wald's χ 2 = 3.13, p = .077) in intervention group from pre-to post-intervention. Decrease in LSMC activation (Wald's χ 2 = 9.20, p = .002) and increase in LSMC-amygdala rsFC (Wald's χ 2 = 4.72, p = .030) related to decreased patient-reported NPS. Increased positive valence across sessions was significantly associated with intervention-related NPS improvement (Wald's χ 2 = 22.92, p < .001). There were no findings for caregiver-reported NPS. Effects were stronger for left postcentral compared to left precentral gyrus. Conclusion: We found tentative evidence that tDCS applied to LSMC during visual attention in older adults with MCI improved NPS via changes in LSMC activation and LSMC-amygdala rsFC, suggesting improved emotion regulation. Patient-reported NPS was more sensitive to these changes than caregiver-reports, and effects were strongest for left postcentral gyrus. Follow-up studies should perform precise mechanistic investigation and efficacy testing.